Effects of an experimental taper period on male and female swimmers - de Arruda, Tarine B.; Kalva-Filho, Carlos A. [UNESP]; Milioni, Fabio [UNESP]; Barbieri, Ricardo A.; Gobbi, Ronaldo B.; Papoti, Marcelo (Edizioni Minerva Medica, 2021)
BACKGROUND: This study investigated the possible influence of the gender on the responses of swimmers during a taper period (TP). METHODS: Ten males (19±3 years and 73.5±7.8 kg) and ten females (17±2 years and 54.7±7.2 kg) swimmers were submitted to a 12-week training, followed by three weeks of the TP. Before and after the TP we evaluated the performance at 100 m freestyle, stroke parameters and lactacidemic responses; lactate minimum intensity (LMI) and stroke parameters associated with LMI and the propulsive force in tethered swimming. TP consisted of 14 sessions with mean volume 2253±1213 m/session at an intensity below than the LMI, 1730±327 m/session at an intensity near the LMI and 1530±1019 m/session at an intensity above the LMI. RESULTS: Significant effects of the genders were observed for LMI and stroke parameters (P<0.001 and η2>0.52 [large]) and propulsive force (P=0.001; η2=0.59 [large]). However, no significant effects of the TP were identified in the performance of the 100 m freestyle (P=0.66; η2=0.006 [small]), propulsive force (P>0.63; η2<0.006 [small]), aerobic parameters (LMI: P=0.32 and η2=0.03 [small]) and mechanical parameters (P>0.23; η2=0.01 [small]). Nonetheless, the peak blood lactate concentrations were improved after TP (P=0.014; η2=0.16 [large]), without significant interactions (P=0.38; η2=0.02 [small]), as well as the mechanical parameters during maximum 100 m freestyle (P<0.04 and η2>0.10 [medium]). CONCLUSIONS: Hence, men and women presenting significantly different values in the age group studied, the responses observed after the TP investigated were the same independent of gender.